The Economic Impact of Living Cell Tissue Products in Treating Diabetic Foot Ulcers and Venous Leg Ulcers in Patients with Commercial Insurance: A Retrospective Matched-Cohort Study. (May 2023) - Barbul, Adrian; Gelly, Helen; Obradovic, Kayla; Landsman, Adam
ABSTRACT: OBJECTIVE: Previous studies demonstrated that costs paid on behalf of Medicare recipients for diabetic foot ulcers and venous leg ulcers treated with cellular and/or tissue-based products (CTPs) varied in part based on the CTP chosen. This study extends previous work to determine how costs vary when paid by commercial insurance carriers. METHODS: A retrospective matched-cohort intent-to-treat design was used to analyze commercial insurance claims data between January 2010 and June 2018. Study participants were matched using Charlson Comorbidity Index, age, sex, type of wound, and geographic location within the US. Patients treated with a bilayered living cell construct (BLCC), dermal skin substitute (DSS), or cryopreserved human skin (CHSA) were included. RESULTS: Wound-related costs and number of CTP applications were significantly lower for CHSA relative to BLCC and DSS at all time intervals (60, 90, and 180 days and 1 year after first application of the CTP). Further, CHSA was associated with significantly fewer amputations at 1 year relative to DSS (14.9% vs 19.7%, P = .03). CONCLUSIONS: There was a statistically significant reduction in cost of treating diabetic foot ulcers (BLCC, DSS, CHSA) and venous leg ulcers (BLCC, CHSA) with CHSA as compared with the other CTPs. These findings are attributed to fewer applications, lower wound care costs, and comparable or reduced incidence of amputation. These commercial insurance data are consistent with prior studies that examined Medicare expenditures.